ANALISIS MODEL BISNIS PETERNAKAN BEBEK DENGAN PENDEKATAN BUSINESS MODEL CANVAS DI KELURAHAN PARINGIN KOTA, KABUPATEN BALANGAN, KALIMANTAN SELATAN - Afritanti, Rizki Diah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Duck farming has opportunity and great potential to support food security and increase rural household income. This study aims to analyze the business model of duck farming in Paringin Kota subdistrict, Balangan Regency using the Business Model Cnavas (BMC) approach. A descriptive qualitatve method was applied with data collected through interviews, observation, and documentation. The value proposition include households, and traditional market traders. The value propotion lies ini providing fresh duck eggs, and processed product (salted eggs). Distribution channels include traditional markets, and social media. The BMC analysis also revealed that product diversification, pathnerships with local SMEs, and the use of digital marketing are key strategies for business sustainability. This study recommends strengthening farme group institutions and government policy support in access to finance and markets.